UX DESIGN EVALUATION OF AN AUGMENTED REALITY SYSTEM FOR HUMAN PHYSICAL TRAINING - Sidhu, Manjit Singh; Iqbal, Javid (Malaysian Journal of Computer Science, 2021)
Technology advancements has enabled dance to be learnt without mirrors or real dance trainer. Distinctive benefits has been contributed by Augmented Reality (AR) technology. Dance trainers are focusing upon implementing dance analysis systems to enhance dance trainee’s artistic skills. AR technology presents new user experience (UX) for learning, instructing, developing and accessing physical dance movements as well as provides scope to expand dance resources and rediscover the learning process. In this research work, we present a novel human physical training system i.e. dance training and analysis that could help individuals in learning selected dance styles which ignites motivation, matches dance steps/body postures and analyzes the performance. This study explored quantitative data by means of statistical tests validation with participants in using the phyisical training system that has facilitated in testing the dance body postures and steps. The work also adopted the user experience (UEQ) questionnaire to perform the UX evaluation. The outcome revealed favaroble results indicating the measurement score of the UEQ six scales to be in the positive range.